2005
DOI: 10.1161/01.cir.0000157155.44008.0f
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Preconditioning Promotes Codifferentiation of Human Fetal Liver CD133 + Stem Cells Into Angiomyogenic Tissue

Abstract: Background-CD133 (AC133) is a surface antigen that defines a broad population of stem cells, including myogenic and endothelial progenitors. CD133 ϩ cells are rare in adult tissues, and the factors that support their differentiation into mature angiomyogenic cells are not known. These hurdles have hampered the use of CD133 ϩ cells for therapeutic purposes. Because human fetal liver is a rich source of CD133 ϩ cells, we sought to identify the growth factors that promote codifferentiation of these cells into ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 38 publications
2
34
0
1
Order By: Relevance
“…Purity for CD133 + colon cancer cells from all tumor samples was greater than 97%. 6 ) from each human tumor were injected subcutaneously in the left flank of 3 mice (8 weeks of age). To determine the minimal amount of cells capable of engraftment, we performed limiting dilution experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Purity for CD133 + colon cancer cells from all tumor samples was greater than 97%. 6 ) from each human tumor were injected subcutaneously in the left flank of 3 mice (8 weeks of age). To determine the minimal amount of cells capable of engraftment, we performed limiting dilution experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Later, it was found on endothelial (4), lymphangiogenic (5), and myoangiogenic (6) progenitors. Although the biological function of CD133 remains unknown, CD133 is recognized as a stem cell marker for normal and cancerous tissues.…”
mentioning
confidence: 99%
“…Among them are mast cells, which increase in number during involution (Qu et al 1995;Tan et al 2004), and myeloid cells (CD45 þ /CD14 þ ), which are present during the proliferative phase. Hemangioma progenitor cells or hemangioma-derived stem cells (HemSCs) have been identified and isolated by us based on the expression of the human stem/progenitor cell marker CD133 (Shmelkov et al 2005). These cells have self-renewal capacity and display multipotential activity, being able to differentiate in vivo into endothelial cells and adipocytes (Khan et al 2008).…”
Section: Mechanism Of Action In Infantile Ihmentioning
confidence: 99%
“…CD133 has been identifed as a pentaspan transmembrane protein in neuroepithelial cells (11) and has been detected in human hematopoietic stem cells (12,13) and several human solid malignancies, such as glioma (5), melanoma (14), osteosarcoma (15) hepatic cancer (16,17), colon cancer (10,18), ovarian cancer (19), and lung cancer (20). A previous report showed that the CD133 + subpopulation in glioma could generate tumors when transplanted into xenogenic immunocompromised mice, and such mice have higher resistance to radiation and chemotherapy (5).…”
Section: Introductionmentioning
confidence: 99%